Experiences of HPV self-collection among Aboriginal and Torres Strait Islander women and people with a cervix - Louise E. Mitchell; Emily Phillips; Chloe J. Jennett; Claire Bavor; Tessa Saunders; Claire Nightingale; Megan A. Smith; Lisa J. Whop (PLoS ONE, 2026)
Since July 2022, Australian guidelines have recommended that anyone eligible for cervical screening be offered a choice between using a self-collected vaginal sample or a clinician-collected cervical sample for Human Papillomavirus (HPV) testing. This study explored cervical screening among 555 Aboriginal and Torres Strait Islander women and people with a cervix, 261 who had screened since the policy change (‘recently screened’). Participants were recruited for an online survey between December-2023 and April-2024. Over half of recently screened participants were offered a choice of collection methods (n = 151, 58%). Of those offered the choice, 67% chose to screen using self-collection (n = 101). In total, 46% (n = 118) of recently screened participants used self-collection, either themselves at home (n = 41, 35%) or the clinic (n = 48, 41%) or assisted by a healthcare provider without a speculum (n = 29, 24%). Among those who collected their own sample (n = 89), the main reasons were it was less embarrassing, they felt in control of their body, and it was less scary. However, only 55% of these participants felt they had enough information to make an informed decision between collection methods. Over half of recently screened participants reported having a clinician-collected sample with a speculum (n = 133, 51%). The majority were not offered a choice of collection method (61%, n = 81), however 38% (n = 50) were and chose a clinician-collected sample. The main reasons for choosing a clinician-collected sample included always having had it done by a healthcare provider, wanting the healthcare provider to have a look or believing the healthcare provider would collect a better sample. This study highlights a preference for HPV self-collection among Aboriginal and Torres Strait Islander women and people with a cervix, including those who already participate in cervical screening. It reinforces the importance of offering all eligible participants a choice of collection methods and supporting informed decision-making.